Impacto de la implementación de un sistema de gestión ambiental en la competitividad de las empresas de construcción colombiana del sector inmobiliario (2023)
Objective MSME construction companies in Colombia have a great impact at an environmental level, so it is necessary to know and understand the different current legal regulations that the country has and for this a classification of these regulations is carried out so that the legal regulations are obtained. current at the level of water, materials, soil and energy. Based on this classification and with environmental regulatory knowledge, internal and external agreements must be reached in the company in order to obtain an Environmental Management System, therefore, in this way, a commitment must be made by the company's management to conduct an initial assessment to identify the environmental impacts of strategic operations